Contact Stres Limit of Gear Materials - Zhu Xiaolu (Jixie chuandong)
The test data of contact fatigue strength of gears for 12 kinds of material like V-Ti spheroidal graphite cast iron,38SiMnMo and 20CrMnMo etc.are presented.The pitting endurance limits σHim and S-N Curves（R=0. 99）for gears of these materials are compared. Then some conclusions about how to make σHim and ZNT Choice are obtained.